Honors Students' Perceptions of Their High School Experiences: The Influence of Teachers on Student Motivation. (January 2014) - Siegle, Del; Rubenstein, Lisa DaVia; Mitchell, Melissa S.
Academic motivation is important for students' task persistence, academic performance, and college selection. The goal of this qualitative study was to understand academic motivation from the students' perspective. Focus group discussions with 28 university honors freshman revealed that students most often attributed their interest and motivation in high school to their interactions with their teachers. These findings supported the theoretical foundations of the Achievement Orientation Model and demonstrated how effective teachers can influence all components of that model as they encourage students' growth and satisfaction (building self-efficacy), as they make the content meaningful and challenging for their students (creating task valuation), and as they shape students' perception of support in their environment through building positive relationships and being knowledgeable about the content (fostering a positive environmental perception). Teachers with extensive depth and breadth of content knowledge are better able to foster student motivation. These teachers have the background to be comfortable differentiating content, straying from the familiar textbook territory, and delving into a variety of instruction strategies, such as in-depth discussions, with their students.